Project management for mere mortals - Baca, Claudia (LiveLessons., 2007)
"Project Management for Mere Mortals is a comprehensive video training course that teaches key techniques, using a live case study that covers all five process groups of project management: initiation, planning, execution, monitoring/controlling, and closing."--Resource description page.